Investigating the Relationship between Audit Quality and Profit Management Case Study: Companies Accepted in Tehran Stock Exchange - AfsarAlimoradi; Sozan Abdulkarim Faraj (QALAAI ZANIST SCIENTIFIC JOURNAL, 2018)
The present research has been performed aiming to investigate the relationship between audit quality and profit management in the companies accepted in Tehran Stock Exchange. The data and information required for doing this research are collected from different sources according to their type. Information related to research literature and theoretical topics have been collected from library resources, academic bases, and foreign and domestic articles. The data needed to calculate research variables have been extracted from "TadbirPardaz" and "RahavardNovin" databases. The Excel and Eviews software have been used to calculate and prepare data for the required research data as well as their analysis. The findings of research indicate a negative and significant relationship between profit management and audit wage. Also, the relationship between profit management and company's size was not accepted and was not confirmed..